Risk, uncertainty and monetary policy - Geert Bekaert; Marie Hoerova; Marco Lo Duca (European Central Bank (ECB), 2013)
The VIX, the stock market option-based implied volatility, strongly co-moves with measures of the monetary policy stance. When decomposing the VIX into two components, a proxy for risk aversion and expected stock market volatility (“uncertainty”), we find that a lax monetary policy decreases both risk aversion and uncertainty, with the former effect being stronger. The result holds in a structural vector autoregressive framework, controlling for business cycle movements and using a variety of identification schemes for the vector autoregression in general and monetary policy shocks in particular. The effect of monetary policy on risk aversion is also apparent in regressions using high frequency data.
Keywords: E44; E52; G12; G20; E32; 330; business cycle; monetary policy; option implied volatility; risk aversion; uncertainty